Development and evolution of the gynoecium in Myrteae (Myrtaceae) - Pimentel, Rafael R.; Barreira, Natalia P.; Spala, Diego P.; Cardim, Nathane B.; Souza, Marcelo C.; Sa-Haiad, Barbara; Machado, Silvia R. [UNESP]; Rocha, Joecildo F.; Santiago-Fernandes, Lygia D. R. (Csiro Publishing, 2014)
Characters of the gynoecium are considered potentially significant for the systematics of Myrtaceae. However, only two such characters - ovule number and placentation - have been addressed from an evolutionary perspective. Colleter presence in flowers is a synapomorphy of Myrtales; however, no morphological and histochemical descriptions of such structures have been done in Myrtaceae. Here we analysed the ontogeny and anatomy of the gynoecium combined with the ontogeny, anatomy, ultrastructure, and histochemistry of the colleters to study the evolution of these characters and map their states in the Myrteae phylogenetic tree. Our findings may help elucidate the evolutionary history of this tribe of fleshy-fruit producers so important towards maintaining ecological balance in the rainforest. Floral anatomy and ontogeny were analysed using light microscopy. Colleter samples were processed using standard methods for light and transmission electron microscopy. The main metabolites in colleters were detected via histochemistry. To map character states the program Mesquite version 2.71 was used. The morphological characters of the South American Myrteae here analysed provided an overview of the evolution of gynoecium - with cauline or carpellate placenta - and of colleters, as well as synapomorphies for the clades Plinia + Myrcia and Eugenia + Pimenta. The presence of two integuments in the ovules associated with sclereids and colleters in the gynoecium and the young fleshy fruit assures the efficient dispersal of their seeds. Our findings regarding gynoecium structural diversity of the tribe Myrteae give a new insight on their morphologically uniform flowers.
Keywords: antomy; colleter; histochemistry; ontogeny; ultrastructure